Management of Community-Acquired Pneumonia in Pediatrics: Adherence to Clinical Guidelines - Tannous, Rim; Haddad, Raymond N.; Torbey, Paul-Henri (Frontiers in Pediatrics, 2020)
Objectives: To evaluate adherence to inpatient care guidelines of pediatric community-acquired pneumonia (CAP). Background: Pediatric CAP is a highly prevalent and morbid infection worldwide. Despite the presence of recommendations for optimal and uniform management, discrepancies with effective management are still reported, raising the necessity to evaluate our local clinical practices. Patients and Methods: A retrospective study was conducted over 3 years on all children hospitalized for CAP at our institution. Adherence to guidelines regarding inpatient care was evaluated with the main focus on the indication of hospitalization, initial antibiotic choice, treatment duration, and hospital stay. A bivariate analysis was performed to identify potential clinical factors influencing adherence rates. Results: A total of 122 children (median age of 3.5 years) were enrolled. Hospital admission was indicated in 47.5 % of patients and was found to be related to the patient’s age, the severity of pneumonia, the presence of an underlying disease and to be driven by the value of serum CRP as well as prolonged fever. Hospitalization lasted for a median of 4 days and was justified in only 23.8% of patients. The choice of antibiotics was relevant in 91.8% of cases with amoxicillin-clavulanate being the most prescribed. Antimicrobial therapy lasted for a median of 10 days and was in accordance with recommendations in 58.3% of patients. No clinical parameter was found to be significantly associated with length of stay or choice and duration of antibiotic therapy. Conclusions: The choice of antimicrobial therapy was found to be consistent with recommendations but adherence to guidelines regarding the treatment duration, the decision and length of hospitalization still need to be improved.